Distinguish Yourself: Get an ORCID. Issue 1 (January 2017) - Simpson, Kathleen Rice
Abstract : Every author needs a unique identifier that works to avoid confusion with others with the same, similarly spelled, or like-sounding names and is maintained over the course of their writing and research career. MCN supports the use of ORCID.